2011
DOI: 10.1111/j.1365-294x.2011.05136.x
|View full text |Cite
|
Sign up to set email alerts
|

On the specificity of avian blood parasites: revealing specific and generalist relationships between haemosporidians and biting midges

Abstract: The study of host-parasite relationships involving vector-borne parasites requires understanding interactions between parasites and vectors. The capacity of haemosporidians to infect insects has clear evolutionary consequences for the transmission of diseases. Here, we investigated (i) the associations between blood parasites, biting midges and birds and (ii) the potential specificity between biting midge and haemosporidian haplotypes. A total of 629 parous biting midges Culicoides and 224 wild birds (belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 43 publications
2
95
2
3
Order By: Relevance
“…Associations between various Culicoides spp. (C. circumscriptus, C. pictipennis, C. festivipennis, C. salinarius, C. duddingstoni, C. kibunensis, C. punctatus, C. simulator and C. segnis) and Haemoproteus lineages have been already published before (Martínez-De La Puente et al 2011, Santiago-Alarcon et al 2012, Synek et al 2013. In our study, we have found three lineages of Haemoproteus infecting two species of Culicoides.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Associations between various Culicoides spp. (C. circumscriptus, C. pictipennis, C. festivipennis, C. salinarius, C. duddingstoni, C. kibunensis, C. punctatus, C. simulator and C. segnis) and Haemoproteus lineages have been already published before (Martínez-De La Puente et al 2011, Santiago-Alarcon et al 2012, Synek et al 2013. In our study, we have found three lineages of Haemoproteus infecting two species of Culicoides.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have shown that some Culicoides spp. have ornithophilic food preferences (Martínez-De La Puente et al 2011, Pettersson et al 2012, Santiago-Alarcon et al 2012. According to these publications, the Bulgarian list of species includes five species feeding on birds (Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialized associations between specific parasites and vectors (20)(21)(22) may drive such heterogeneity, although a recent analysis suggests that parasitehost compatibility is also important (23), and local coevolutionary relationships between parasites and their hosts likely influence geographic distributions of both host and parasite populations (11,14,15). However, most regional studies of these parasites have focused on individual host species (24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…are known for their low specificity and broad host range which allows for host switching between different mosquito vectors as well as avian hosts. 47 Host switching could also cause a parasite to undergo a change in virulence 48 which could translate into an acute infection. Even if penguins survive these new infections during rehabilitation, they could become carriers and introduce this Plasmodium species into breeding colonies, thereby exposing the population to a new hitherto unknown Plasmodium.…”
Section: Discussionmentioning
confidence: 99%